Capacity Building and Participation of Private Health Centers in Tuberculosis Case-Finding in Bangli Regency, Bali Province - Yuliyatni, Putu Cintya Denny; Sari, Komang Ayu Kartika; Cempaka, Ayu Rissa (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
The 2017-2019 Bangli Regency Health Office data shows that Tuberculosis (TB) case finding in Bangli Regency was below the national target. An evaluation of TB surveillance found that the participation of Private health centers in reporting and finding TB cases remained low in Bangli. Based on this finding, a workshop on strengthening private health service networks in Bangli was conducted online. The topics delivered in the workshop included TB case finding through the public-private mix, the role of private health centers in TB case finding and the results of the evaluation of the TB surveillance system in Bangli Regency. The workshop was attended by 47 participants from various Private health centers in Bangli. The workshop was evaluated using a questionnaire measuring knowledge of TB and TB surveillance. The result shows that most respondents had good knowledge of TB and TB surveillance systems; however, the low participation rate which was only 50% of the target, made it important to send a summary of workshop materials designed in the form of booklets. These booklets have been distributed to all Private health centers, especially those who did not participate in the workshop, to increase knowledge and willingness to participate in TB case finding in Bangli Regency.